Developing of protocol for egg incubation and larval culture of Tachypleus gigas muller - Mat Isa, Mohamad Faizul (2013)
Culture of horseshoe crab in laboratory for future restocking most likely is the best solution so far in order to reduce the possibility of extinction of this species. Establishment of suitable protocols is crucial to successfully hatch the eggs and culture the larvae of Tachypleus gigas. Studies were carried out at MTDC Laboratory, Putra Science Park, Universiti Putra Malaysia, Serdang, Selangor. The objectives of this study were divided into two main parts. First, to determine the effects of salinity, watering frequency and incubation medium on the hatching of T. gigas eggs. Second, to determine the effects of salinity, temperature, culture medium and stocking density on growth and survival of T. gigas larvae. Eggs,larvae and sand were collected from three natural spawning sites in Sitiawan (Perak), Banting (Selangor) and Muar (Johor), Malaysia. This research consists of seven experimental studies. Three experiments were carried out on eggs and four experiments on larvae. In the first, second and third experiment, effects of water salinities (15, 20, 25, and 30 ppt), watering frequencies (once in 1, 3 and 6 day/s), and different incubation medium (water and sand) on the incubated eggs were investigated. As for the fourth, fifth, sixth and seventh experiment, effect of salinities (15, 20, 25, 30 ppt), temperatures (ambient, 30 and 32˚C), using sand and water medium, and stocking densities on horseshoe crab larvae was studied. Results from experiment 1, showed that at the end of the incubation period,watering with salinity of 25-30 ppt produced significantly larger eggs diameter (P<0.05) while highest percentages of hatching at 30 ppt salinity. In experiment 2,it was found that percentages of hatching were significantly higher (P<0.05) when watered once a day and three days. As for experiment 3, at the end of the incubation period, there was no significant different (P>0.05) in the eggs diameter and percentage of hatching between sand and water medium. Results for the fourth experiment (salinity) on instars 1 to 4 (1st to 6th month) and instars 4 to 7 (6th to 12th month) only showed significant different (P<0.05) in percentage of survival at 4th instar stage while all parameters (prosomal width,weight and survival) were significantly different (P<0.05) from 4 to 7th instar stages. In the fifth experiment, percentage of survival was highest (P<0.05) at 30˚C. As for the sixth experiment, significant increments (P<0.05) were observed for prosomal width, weight and survival when cultured in sand at the end of the 12 month period. In the seventh experiment, no significant different (P>0.05) for the prosomal width, weight and survival of T. gigas larvae were observed when cultured at stocking densities of 20, 40 and 60 larvae/L. Based on the findings of this study, it can be concluded that the most suitable salinity and watering frequency for the incubation of horseshoe crab eggs are between 25 to 30 ppt and once in 3 days, respectively. Both sand and water aresuitable media to incubate T. gigas eggs. As for the experiments on larvae, the best salinity for optimum survival is between 20 to 30 ppt at temperature of 30˚C. Meanwhile stocking density and culture media does not affect the growth and survival of the larvae. Observation on the growth of T. gigas larvae throughout the study period showed that prosomal width may not be a reliable indicator of growth since the size will increase significantly whenever larvae molt. Therefore it is better to measure the growth of T. gigas larvae through weight increment.